Efficacy and safety of itraconazole pulse therapy: Brazilian multicentric study on toenail onychomycosis caused by dermatophytes - Ramos-e-Silva, M.; Marques, Silvio Alencar [UNESP]; Gontijo, B.; Zaitz, C.; Campbell, I; Veloso, S. T. (Elsevier B.V., 1998)
Background Itraconazole is a large spectrum triazole with known efficacy in both continuous and pulse therapy for various mycoses.Objectives Evaluate the efficacy and tolerability of itraconazole pulse therapy for onychomycosis of the toenails due to dermatophytes, in a prospective, open, non-comparative and multicentric investigation.Patients and methods the trial was completed by 72 patients of an initial total of 89. Treatment consisted of four cycles of itraconazole, 200 mg twice a day, for seven consecutive days each month. Patients were evaluated clinically, mycologically and biochemically before, during and at the end of the investigation, and were divided into two groups according to the measure of normal portion of the most affected nail (target nail), as follows: Group 1. 0-5.9 mm; and Group 2: more than 6 mm.Results Improvement was satisfactory and progressive. Results were statistically significant, when comparing the three moments of the study: pre-treatment, end of therapy (fourth month) and follow-up (ninth month) in both groups.Conclusions Itraconazole pulse therapy was efficient and safe for the treatment of onychomycosis caused by dermatophytes, although a much higher daily dosage than the known continuous administration was used. Group 1, with nails initially more extensively affected, had a more evident improvement, by the mean variation in millimeters of normal portion of the target nail. This group showed a very satisfactory response, although not reaching total cure, thus demonstrating the great importance of early treatment of this disease. A residual therapeutic effect is maintained even after suspension of the drug. Group 2 obtained better total cure rates, and four pulses were, in general, sufficient, whereas more cycles would have been beneficial for the Group 1 patients with more extensive involvement. (C) 1998 Elsevier B.V. B.V. All rights reserved.
Keywords: dermatophytes; itraconazole; onychomycosis; pulse therapy; therapy